МУЛЬТИКУЛЬТУРНА ОСВІТА: КОНЦЕПТУАЛЬНІ ЗАСАДИ - Пришляк Оксана Юріївна (World Science, 2019)
The article describes the essence of multicultural education, which in the modern world acquires the leading concept of the unity of world cultures, the search for unifying components and ways of their realization. The article deals with the interpretation of multicultural education, new approaches to the organization of multicultural professional education, factors and principles of multicultural education, model of multicultural education are disclosed.